2020
DOI: 10.1111/hepr.13468
|View full text |Cite
|
Sign up to set email alerts
|

Wisteria floribunda agglutinin‐positive human Mac‐2‐binding protein as a predictive marker of liver fibrosis in human immunodeficiency virus/hepatitis C virus coinfected patients

Abstract: Aim: In human immunodeficiency virus (HIV) and hepatitis C virus (HCV) coinfected patients, the progression of liver failure is reported to be more aggressive than that in HCV monoinfected patients. Wisteria floribunda agglutinin-positive human Mac-2-binding protein (WFA + -M2BP) is well recognized as a liver fibrosis glycobiomarker with a unique fibrosis-related glycoalteration. We analyzed HIV/HCV coinfected patients' M2BP levels as a possible marker for predicting liver fibrosis.Methods: M2BP was measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition, compared with the co‐infected group, patients with HCV mono‐infection had a significantly higher APRI score, although there were no significant differences between groups in terms of serum M2BPGi and elastography evaluated by TE and MRE. However, in a recent propensity score‐matched cohort, M2BPGi levels were significantly higher in patients with HIV/HCV co‐infection compared with levels in the HCV mono‐infected group 35 . Such a discrepancy probably contributed to the difference in study design, as our report enrolled unmatched patients with or without HIV infection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, compared with the co‐infected group, patients with HCV mono‐infection had a significantly higher APRI score, although there were no significant differences between groups in terms of serum M2BPGi and elastography evaluated by TE and MRE. However, in a recent propensity score‐matched cohort, M2BPGi levels were significantly higher in patients with HIV/HCV co‐infection compared with levels in the HCV mono‐infected group 35 . Such a discrepancy probably contributed to the difference in study design, as our report enrolled unmatched patients with or without HIV infection.…”
Section: Discussionmentioning
confidence: 72%
“…However, in a recent propensity score-matched cohort, M2BPGi levels were significantly higher in patients with HIV/HCV co-infection compared with levels in the HCV mono-infected group. 35 Such a discrepancy probably contributed to the difference in study design, as our report enrolled unmatched patients with or without HIV infection. In conclusion, our data showed that HCV eradication with EBR/ GZR therapy was associated with significant fibrosis improvement, as measured using MRE, TE and serum fibrosis markers.…”
Section: Discussionmentioning
confidence: 92%
“…In such cases, we will have to monitor the graft liver using various reported markers of liver fibrosis, scores, and special ultrasound examinations to prevent refibrosis leading to graft failure. [35][36][37][38][39] Our study was associated with some limitations. First, despite the retrospective design, the specific patient population was still relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported that M2BP levels help diagnose and predict the recurrence of HCC in HBV-and HCV-infected patients or patients with nonalcoholic fatty liver disease. (3,4,(8)(9)(10) Patients with chronic viral hepatitis, regardless of the degree or severity of brosis, have elevated serum levels of M2BP, indicating an increased occurrence of HCC. (2,11) A study on liver stiffness also indicated that M2BP might be associated with the development of HCC, independent of brogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the amount of M2BP attached to Wisteria oribunda agglutinin (WFA) signi cantly positively correlates with the degree of liver brosis (1) and acts a predictor of liver cirrhosis and hepatocellular carcinogenesis in chronic hepatitis C cases. (2,3) Furthermore, in chronic hepatitis B patients with hepatocellular carcinoma (HCC) diagnosed using imaging tests, a signi cant increase in M2BP is observed, suggesting the possibility of early diagnosis using M2BP level determination. (4) We performed living donor liver transplantation (LT) for patients with decompensated cirrhosis and histological diagnosis of the whole liver removed from the recipient during LT. We have previously often detected the presence of small and occult HCCs in removed livers, which cannot be detected using preoperative ultrasonography or computed tomography (CT), indicating a limitation to cancer diagnosis using existing preoperative tests.…”
Section: Introductionmentioning
confidence: 99%